Early and Mid-Term Outcomes of Coronary Protection during Transcatheter Aortic Valve Replacement: A Single-Center Retrospective Analysis - Jiawei Zhou; Yuehuan Li; Jinglun Shen; Kaisheng Wu; Jiangang Wang; Yi Yu; Haibo Zhang (Reviews in Cardiovascular Medicine)
Background: Coronary obstruction (CO) is a fatal complication in transcatheter aortic valve replacement (TAVR). However, data on the outcomes and details of coronary protection (CP) use in TAVR are limited. Methods: We retrospectively analyzed the patients who had undergone CP during TAVR at our tertiary cardiac center from March 2017 to January 2024. CP was achieved by an undeployed coronary balloon or stent positioned within the coronary artery, which releases the stent at CO occurrence. Patients' computed tomography (CT) evaluation reports and perioperative and follow-up outcomes were reviewed. Results: A total of 33 out of 493 patients (6.7%) underwent CP during TAVR due to the high risk of CO based on preoperative CT analysis. The mean sinus dimensions measured 30.1 ± 3.6 mm, 29.2 ± 3.4 mm, and 30.4 ± 3.7 mm for the left, right, and non-coronary sinus, respectively. The average left main height was 11.7 mm, and the right coronary height was 14 mm. Self-expanding valves were used in 93.9% of the patients. Coronary balloons were used for CP in 30 patients, whereas undeployed coronary stents were used in three cases. A total of 36 coronary arteries were protected, including 28 left coronary arteries alone, two right coronary arteries alone, and three dual coronary arteries. Eight patients (24.2%) developed CO and underwent stent release. The in-hospital and 30-day all-cause mortality rates were 9.1% and 0%, respectively. The median follow-up time was 10 months, and only one patient died 2 months after discharge due to stroke during the follow-up. Conclusions: Pre-emptive coronary balloons or stents for CP allow for revascularization in the shortest possible time in the event of CO. Early and mid-term outcomes of CP during TAVR in patients with a high risk of CO show that CP is safe and feasible.